ANALYSIS OF THE APPLICATION OF TIME MANAGEMENT USING THE CPM METHOD IN THE REHABILITATION WORK PROJECT OF THE DISDIKBUDPORA HALL BUILDING - Shinta Ayu Ramadhany; Putri Anggi Permata Suwandi; Diah Rahmawati; Anggits Burhanudin; Yesenia Laura; Mohammad Mukhdif Al-Afghoni (DEARSIP : Journal of Architecture and Civil, 2026)
Time management is one of the important factors in the successful implementation of construction projects because it is directly related to time efficiency, cost, and quality of work. In the Semarang Regency Disdikbudpora Hall Rehabilitation Project, the preparation of the implementation schedule is still not optimal due to the determination of the duration of work that has not considered the complexity and relationship between activities properly. This study aims to analyze the application of time management using the Critical Path Method (CPM) method to obtain a more effective project implementation duration and identify activities that are on the critical path. The research method used is a quantitative descriptive method by utilizing primary data in the form of field observations and secondary data in the form of time schedules, weekly reports, work drawings, and Cost Budget Plans (RAB). The analysis was carried out using the CPM method through forward pass, backward pass, and total float to determine the critical trajectory of the project. Data processing is done using Microsoft Excel and network visualization is created using AutoCAD. The results showed that the normal duration of project completion based on the CPM method is 54 working days, 3 days faster than the existing implementation schedule of 57 calendar days. Activities included in the critical path include preparatory work, certain earthworks and foundations, concrete work, wall pairing, floor and wall coverings, and painting work. Activities on critical lines have a total float value of zero, so delays in the work will affect the overall duration of project completion. Based on the results of the analysis, the application of the Critical Path Method (CPM) has proven to be effective in optimizing project scheduling because it is able to identify critical activities and accelerate project completion time. This method can be used as a reference in controlling the implementation time of construction projects to be more efficient and planned.